Information Security Governance Framework in Public Cloud a Case in Low Resource Economies in Uganda - Fredrick Kanobe; SP Sambo; Billy Mathias Kalema (Politeknik Negeri Cilacap, 2022)
The study aimed at exploring the critical enablers to the development and usage of information security governance frameworks for cloud computing in Uganda. The study was motivated by the continuous information security governance challenges in the Public Cloud. The theoretical frameworks that underpinned this study included; Contingency management theory, the Risk Management framework, the Technological Organisational and Environmental (TOE) model and the Information Security Governance model. This study adopted a quantitative research approach to obtain data through a survey. Five key factors for information security governance were identified: a) Technological factors: flexibility, scalability, availability, agility, data protection governance, trust of cloud, data source, maintenance, data retention and policy. b) Organisation: size and structure of the organisation, top management support. c) Environmental factors: governance and regulation, marketing, vendor, resource availability, obsoleteness. d) Individual: user resistance, attitude, skills, belief and learnability. e) Risk management and control factors: risk assessment, disaster recovery, access and authorisation control, monitoring, auditing, and process risk control. The study contributes to theory and practice in information security. The developed framework and its accompanying model helped to inform public departments, organisational top management and information security strategies to avoid excessive information risks and potential regulatory compliance failures in public cloud. The study was inclined on subjective information security, which alone may not fully address all information security problems in a public cloud. Therefore, it is recommendable that future research studies on objective security in public cloud